An improved elasto-plastic constitutive model for the exquisite description of stress-strain hysteresis loops with cyclic hardening and softening effects. (November 2020) - Xu, Li-Yan; Fan, Jian-Sheng; Yang, Yue; Tao, Mu-Xuan; Tang, Zhen-Yun
Abstract: In this study, a finite cyclic elasto-plastic constitutive model is developed to simulate the cyclic hardening and softening of the low-yield-point steel BLY160. Compared with existing models, an improved description of the stress-strain hysteresis loops is achieved by introducing a modified Chaboche kinematic hardening rule and a nonlinear isotropic hardening rule extended with a strain memory surface. In the proposed kinematic hardening rule, the backstress is decomposed into three parts for short, middle, and long ranges, with each of them obeying an Armstrong-Frederick (A-F) evolution rule consisting of a linear hardening and dynamic recovery term. To incorporate the significant effect of the kinematic hardening rule on the shape change in hysteresis loops, a dynamic recovery coefficient is postulated herein to develop with not only the accumulated plastic strain but also the memorized strain range. In addition, a hardening factor is introduced to the linear hardening term to consider the different plastic moduli of monotonic and cyclic deformations. The model parameters are identified in an exquisite manner by discriminating the contributions of the isotropic and kinematic components to the cyclic hardening and softening phenomena, which is implemented through a quantitative evaluation of the tested hysteresis loops. The comparison between the numerical prediction and experimental results indicates that the developed constitutive model can elaborately simulate the cyclic behaviour of the investigated steel. The results demonstrate that the entire evolution process of the stress-strain hysteresis curve characterized by the cyclic hardening and softening, transient Bauschinger effect, and strain-range dependence can be adequately described by the proposed model. Graphical abstract: Image 1 Highlights: The kinematic hardening has a significant influence on the shape change of hysteresis loops. Obvious different plastic moduli exist between the monotonic and cyclic deformation. A constitutive model for exquisitely simulating the hysteresis loops is developed. Strain range dependence is incorporated in both kinematic and isotropic hardening rules. Quantitative evaluation of the hysteresis loops helps calibration of model parameters.